A Comparative Study on Engine Performance of Modified Diesel Engine with Dual Biogas and Pure Biogas Fuel - ฝั้นแก้ว, ประเทือง; พงศ์พุฒิ, คณิน; พึ่งสุข, บดีศร; ณ ลำปาง, พุฒิพงศ์ (RMUTL Engineering Journal, 2017)
This paper presents a comparative study of engine performance on a modified engine to use Biogas dual fuel. The engine used in this study was a small 353 cc, 7 HP Mitsubishi diesel, model DI-700. This engine powered a 3KW generator which illuminated an electric light bulb. Before adapting the engine to use Biogas Dual fuel, the compression ratio was 18:1. The experiment indicated that the most efficient ratio of diesel fuel to Biogas is 30:70. At this ratio there is no sign of engine failure at peak engine load. The highest electrical load achieved was 3000 Watts. The ratio of Biogas consumption was 24 liter/min and the ratio of diesel consumption was 10cc/min. After modifying the Diesel engine to be a gasoline engine, the engine power was decreased to 9.88:1 while using only Biogas. According to the results of using only Biogas, it appears the highest efficiency of the engine is 6.95% with the highest electrical load of 500 Watts, biogas consumption was 1.7 liter/min. When the results are calculated the unit cost of using the diesel engine with Biogas is 4.02 baht per kilowatt-hour. For the modified diesel engine using only Biogas the unit cost is 3.44 baht per kilowatt-hour.